Odpowiedzi

2010-04-11T11:54:04+02:00
0
24
-16
-24
22:-8=2,5 - coś takiego
2
32
80
43
1
-3
2
2010-04-11T11:54:43+02:00
2*(-3)+6=0
-5*(-8)-16=24
2*(-5)+3*(-2)=-16
8-6*(-5)=38
6-(-16):(-8)=4
5*(-2)-(-2)*6=2
(2-6)*(-8)=32
-5*(-6-10)=80
-3*(-1)-(-10)*4=43
(-5-6):(-11)=1
24:(-3-5)=-3
(-8+30):(-7-4)=-2
2010-04-11T11:57:44+02:00
2*(-3)+6= -6+6=0
-5*(-8)-16=40-16=24
2*(-5)+3*(-2)=-10+(-6)= -16
8-6*(-5)=8-(-30)= 38
6-(-16):(-8)=22:(-8)= - 2,75
5*(-2)-(-2)*6= -10 - (-12)= 2
(2-6)*(-8)=-4*(-8)= 32
-5*(-6-10)=-5* (-16)= 80
-3*(-1)-(-10)*4=3- (-40)= 43
(-5-6):(-11)=-11: (-11)= 1
24:(-3-5)=24: (-8)= -3
(-8+30):(-7-4)=22: (-11) = - 2